EVALUATION OF THE TOXICITY OF DIFFERENT NICOTINESULFATE CONCENTRATIONS IN CONTROLLING NYMPHALINSTARS AND ADULTS OF CABBAGE APHID BREVICORYNEBRASSICAE (L.) ( HOMOPTERA: APHIDIDAE ) - Abdul-Hay, Hind; Hamad, Mohammed (Iraqi Journal of Science, 2024)
The aim of this project is to study the efficacy of nicotine (as nicotine sulfate)extracted from tobacco by- products of the Iraqi Tobacco and Cigarettes Industryagainst cabbage aphid Brevicoryne brassicae (L.). On the basis of LC50 values,laboratory data have indicated a positive correlation between these values andprogress of insect life cycle . The LC50 values for the fourth nymphal instar were 4.9more than first instar; while it was for apterae 6.5 times more than the first instar fornicotine sulfate. The alatae were more susceptible to insecticide than apterae, whereLC50 values for apterae were 1.03 times more than that for alatae LC90 for nicotinesulfate on all stages follow the same trend as for LC50 but with higher values.Finally, we recommend the use of nicotine sulfate as an insecticide for the control ofcabbage aphid instead of the widely used pesticides compounds which areenvironmental pollutants